Javanese Coastal Community Value System: Study of the Muria Raya Coastal Community - Falaq, Yusuf; Wasino, Wasino; Utomo, Cahyo Budi; Brata, Nugroho Trisnu (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research discusses the value system of Javanese coastal communities, especially the Jepara community as one of the areas in Muria Raya. The value system in this article focuses on the knowledge value system, belief value system and arts value system. Coastal communities do not only refer to entities that live on the coast, but also entities that produce systems of knowledge, beliefs and arts that have certain patterns. This community collectivity then gave birth to the identity of coastal communities. The unique thing about the Muria Raya area was that it was previously an island on the spice trade route between the Middle East and Maluku before the 17th century under the leadership of Queen Kalinyamat, which then due to sedimentation in the Muria Strait became one unit with the mainland of Java Island. So the characteristics of the community's value system are different from other communities on the north coast of Java. A qualitative approach was chosen with ethnographic analysis as a sharpening knife in this research. The results show that the Jepara people as one of the coastal entities living in the Muria Raya area have a very diverse knowledge value system. They are very closely related to the history of the Kalinga Kingdom and the Kalinyamat Kingdom, so that topography, natural conditions, rituals and religious traditions as well as forms of art and culture cannot be separated from the influence of these two kingdoms.